Quantification of t-tubule area and protein distribution in rat cardiac ventricular myocytes - Pásek, M; Brette, F; Nelson, A; Pearce, C; Qaiser, A; Christe, G; Orchard, C H (Progress in biophysics and molecular biology, 2008)
The transverse (t-) tubules of cardiac ventricular myocytes are invaginations of the surface membrane that form a complex network within the cell. Many of the key proteins involved in excitation-contraction coupling appear to be located predominantly at the t-tubule membrane. Despite their importance, the fraction of cell membrane within the t-tubules remains unclear: measurement of cell capacitance following detubulation suggests approximately 32%, whereas optical measurements suggest up to approximately 65%. We have, therefore, investigated the factors that may account for this discrepancy. Calculation of the combinations of t-tubule radius, length and density that produce t-tubular membrane fractions of 32% or 56% suggest that the true fraction is at the upper end of this range. Assessment of detubulation using confocal and electron microscopy suggests that incomplete detubulation can account for some, but not all of the difference. High cholesterol, and a consequent decrease in specific capacitance, in the t-tubule membrane, may also cause the t-tubule fraction calculated from the loss of capacitance following detubulation to be underestimated. Correcting for both of these factors results in an estimate that is still lower than that obtained from optical measurements suggesting either that optical methods overestimate the fraction of membrane in the t-tubules, or that other, unknown, factors, reduce the apparent fraction obtained by detubulation. A biophysically realistic computer model of a rat ventricular myocyte, incorporating a t-tubule network, is used to assess the effect of the altered estimates of t-tubular membrane fraction on the calculated distribution of ion flux pathways.
Keywords: krysa rodu Rattus; Animals; sarkolema; Sarcoplasmic Reticulum; Heart Ventricles; proteiny; zvířata; Myocytes, Cardiac; Proteins; Sarcolemma; Rats; sarkoplazmatické retikulum; kardiomyocyty; srdeční komory